A secondary meta‐synthesis of qualitative studies of gender and access to cardiac rehabilitation. (2nd February 2015) - Angus, Jan E.; King‐Shier, Kathryn M.; Spaling, Melisa A.; Duncan, Amanda S.; Jaglal, Susan B.; Stone, James A.; Clark, Alexander M.
Abstract Aims To discuss issues in the theorization and study of gender observed during a qualitative meta‐synthesis of influences on uptake of secondary prevention and cardiac rehabilitation services. Background Women and men can equally benefit from secondary prevention/cardiac rehabilitation and there is a need to understand gender barriers to uptake. Design Meta‐method analysis secondary to meta‐synthesis. For the meta‐synthesis, a systematic search was performed to identify and retrieve studies published as full papers during or after 1995 and contained: a qualitative research component wholly or in a mixed method design, extractable population specific data or themes for referral to secondary prevention programmes and adults ≥18 years. Data sources Databases searched between January 1995–31 October 2011 included: CSA Sociological Abstracts, EBSCOhost CINAHL, EBSCOhost Gender Studies, EBSCOhost Health Source Nursing: Academic Edition, EBSCOhost SPORTDiscus, EBSCOhost SocINDEX. Review methods Studies were reviewed against inclusion/exclusion criteria. Included studies were subject to quality appraisal and standardized data extraction. Results Of 2264 screened articles, 69 were included in the meta‐method analysis. Only four studies defined gender or used gender theories. Findings were mostly presented as inherently the characteristic of gendered worldviews of participants. The major themes suggest a mismatch between secondary prevention/cardiac rehabilitation services and consumers' needs, which are usually portrayed as differing according to gender but may also be subject to intersecting influences such as age or socioeconomic status. Conclusion There is a persistent lack of theoretically informed gender analysis in qualitative literature in this field. Theory‐driven gender analysis will improve the conceptual clarity of the evidence base for gender‐sensitive cardiac rehabilitation programme development.